Career Development Disparities: Private vs. State Higher Education Lecturers in Indonesia - Wahyuningsih , Sri; A.S , Shamsudin (Journal of Ecohumanism, 2025)
Higher education in Indonesia, both state and private higher education, is a national instrument in improving the quality of life in society, state and nation. The agenda of improving the quality of higher education cannot be separated from improving the quality of lecturers’ career development. Whilst this career development should be similar at all higher education institution, the career development among lecturers at private higher education is somehow behind compared to those at the state higher education institutions. This paper is written based on a study examines the influence of competency factor, organizational culture and achievement motivation on work performance and career development of lecturers at private higher education in Indonesia. The study also looks into lecturer work performance as a mediator variable for the relationship between organizational culture and lecturer career development, and lecturer work performance as a mediator variable for the relationship between achievement motivation and lecturer career development. A total of 210 questionnaires were distributed to research locations and 192 (90%) data is processed using PLS Smart4 Structural Equation Modeling (SEM) statistics. The results of the study show that organizational culture, competency and achievement motivation have direct, positive and significant influence on the work performance of lecturers at private higher education in Indonesia. Furthermore, organizational culture and work performance also have direct and significant influence on lecturer career development. These are similar findings for lecturers at the state higher institution. However, the study findings reveal that neither achievement motivation does not have positive and significant effect on lecturer career development, nor, work performance has full mediation (partial mediation) for the relationship between organizational culture and lecturer career development. Moreover, the relationship between achievement motivation and lecturer career development is not mediated by lecturer work performance. It is concluded that the reasons behind this related to the heavy teaching workload, limited financial resources and unachieved status and reputation as the state higher education institutions.